The Role of Customary Law in Forest Governance and Conservation in Jambi, Indonesia: A Case Study of Makekal Hulu Village within the Customary Territory of the Suku Anak Dalam - Burhanuddin; Nova Elsyra; Joko Sunaryo; Syahwami; Helva Rahmi; Hamirul (Enigma in Cultural, 2024)
Indonesia's forests face increasing pressures from deforestation and degradation. While national laws exist to protect these vital ecosystems, their implementation often faces challenges, particularly in areas inhabited by indigenous communities with distinct customary laws and practices. This study examines the role of customary law (adat law) in forest governance and conservation in Jambi Province, Indonesia, focusing on Makekal Hulu village within the customary territory of the Suku Anak Dalam. This qualitative study employed a case study approach. Data were collected through semi-structured interviews with adat leaders, community members, government officials, and NGO representatives. Focus group discussions were conducted to gather diverse perspectives on forest management practices. Relevant documents, such as adat regulations, government policies, and NGO reports, were also analyzed. Additionally, data was utilized to enhance understanding of resource use dynamics and land-use change patterns. The findings reveal that adat law plays a significant role in regulating access to and use of forest resources in Makekal Hulu. Adat institutions, led by the village elder and guided by customary beliefs, enforce rules related to logging, hunting, and land clearing. These rules often complement national laws, providing a localized and context-specific approach to forest management. However, challenges exist in harmonizing adat law with national legislation, particularly concerning land tenure conflicts and external pressures from logging and plantation interests. In conclusion, this study highlights the importance of recognizing and incorporating adat law into forest governance frameworks in Indonesia. By integrating traditional knowledge and practices with national policies, a more effective and sustainable approach to forest conservation can be achieved. This requires collaboration between government agencies, adat communities, and civil society organizations to ensure that adat law is respected and supported within the broader legal framework.